Perlindungan Hukum Terhadap Konsumen Dalam Perjanjian Pendahuluan Jual Beli Rumah di Wilayah Kecamatan Siak Hulu Kabupaten Kampar - Fahrul Rozi; Busyra Azheri; Yussy Adelina Mannas (Universitas Ekasakti, 2024)
Developers can carry out marketing or sales of the houses they build with one of the conditions, namely that the developer has carried out housing construction of at least 20% (twenty percent). However, this is still being violated by the developer, where the developer has done marketing or selling houses using model houses. The problems that can be raised in this thesis are How Legal Protection for Consumers is in the Preliminary Agreement for the Sale and Purchase of Houses in the Siak Hulu District, Kampar Regency, What are the legal consequences for developers who enter into the Preliminary Agreement for the sale and purchase of houses in the Siak Hulu District, Kampar Regency, and what are the forms of supervision? against developers who enter into Preliminary Agreements for Sale and Purchase of Houses in the Siak Hulu District, Kampar Regency. The research method used in this study uses empirical juridical methods, its nature, this research is a descriptive analysis research. The collection method was carried out by field research (interviews) and library research (library research).